The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.jacc.2006.08.048
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Normal Exercise Myocardial Perfusion Imaging and Exercise Echocardiography

Abstract: Both exercise MPI and exercise echocardiography have high NPVs for primary and secondary cardiac events. The prognostic utility of both modalities is similar for both men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
219
4
19

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 428 publications
(267 citation statements)
references
References 161 publications
19
219
4
19
Order By: Relevance
“…21 Although an abnormal stress echocardiogram correlates with a high cardiac event rate in women, a recent meta-analysis comparing dobutamine stress echocardiography to exercise single photon emission computed tomography (CT) (SPECT) MPI revealed a yearly rate of 0.75% of cardiovascular death and MI in the setting of a low-risk dobutamine echocardiogram compared with 0.3% per year in low-risk stress MPI. 28 The authors concluded that stress echocardiography may underestimate risk in women with less advanced CAD because in the ischemic cascade, perfusion abnormalities detected by SPECT MPI precede the wall-motion abnormalities detected by stress echocardiography. Wall-motion abnormalities often occur in the setting of advanced stenosis and less predictably in myocardium supplied by mild-to-moderate coronary artery stenoses.…”
Section: The Clinical Role Of the Exercise Electrocardiogram: Is It Amentioning
confidence: 99%
See 1 more Smart Citation
“…21 Although an abnormal stress echocardiogram correlates with a high cardiac event rate in women, a recent meta-analysis comparing dobutamine stress echocardiography to exercise single photon emission computed tomography (CT) (SPECT) MPI revealed a yearly rate of 0.75% of cardiovascular death and MI in the setting of a low-risk dobutamine echocardiogram compared with 0.3% per year in low-risk stress MPI. 28 The authors concluded that stress echocardiography may underestimate risk in women with less advanced CAD because in the ischemic cascade, perfusion abnormalities detected by SPECT MPI precede the wall-motion abnormalities detected by stress echocardiography. Wall-motion abnormalities often occur in the setting of advanced stenosis and less predictably in myocardium supplied by mild-to-moderate coronary artery stenoses.…”
Section: The Clinical Role Of the Exercise Electrocardiogram: Is It Amentioning
confidence: 99%
“…35, 3, 149-155 (2012) myocardial areas perfused by a less critical stenosis, stress echocardiography may underestimate cardiovascular risk in women with less advanced CAD. 28 The additional imaging information provided by stress echocardiography provides improved diagnostic and prognostic accuracy in women at risk for CAD compared to ETT. 27 In addition, a unique benefit of stress echocardiography for evaluating at-risk women is the absence of radiation exposure compared with other noninvasive imaging techniques (eg, SPECT, cardiac CT, coronary artery calcium [CAC] scoring).…”
Section: The Clinical Role Of the Exercise Electrocardiogram: Is It Amentioning
confidence: 99%
“…Prognostic information is useful in cardiac risk stratification and subsequent clinical management. Also, accurate risk stratification has become increasingly important in optimizing patient outcomes and containing rapidly escalating medical care costs [9]. Similarly, it is important to assess the prognostic value of negative stress CMR from possibility of decreasing unnecessary additional tests and interventions.…”
Section: Introductionmentioning
confidence: 99%
“…This is not only true for patients with greater extent, severity, and reversibility of MPS abnormalities, but also for those with normal MPS findings. 1 The salutatory prognosis of those with a normal MPS test has lead to the implication of a ''warranty period'' following a normal SPECT stress test.While tempting to generalize this ''warranty period'' to all patients undergoing MPS, rates of freedom from adverse cardiac events differ significantly for patients with normal exercise MPS as compared to patients with normal pharmacological MPS. 2 The reasons for these observed differences based on the method of hyperemia induction may seem intuitive; patients who undergo pharmacological MPS tend toward older age, greater numbers of CAD risk factors, increased non-cardiac co-morbidities and reduced functional status, a known powerful predictor of mortality.…”
mentioning
confidence: 99%
“…This is not only true for patients with greater extent, severity, and reversibility of MPS abnormalities, but also for those with normal MPS findings. 1 The salutatory prognosis of those with a normal MPS test has lead to the implication of a ''warranty period'' following a normal SPECT stress test.…”
mentioning
confidence: 99%